Mission vegan : wildly delicious food for everyone - Bowien, Danny; Goode, J. J. (Ecco, an imprint of HarperCollinsPublishers, 2022)
The cofounder and chef of the famous Mission Chinese Food restaurants in San Francisco and New York, making it his mission to find inspiration, joy, and flavor in food, presents vegan recipes geared for the home cook, keeping the emphasis on experimenting in the kitchen and big flavor.